Impact of Black Pepper (Piper nigrum) Powder on Lipid Profile Parameters Among Subjects with Non-Alcoholic Fatty Liver Disease (NAFLD) - Beenish; Saxena Suyash; Kifayat Mirza; Shruti (BIO Web of Conferences)
Non-alcoholic fatty liver disease (NAFLD) is closely associated with dyslipidemia, a critical risk factor for cardiovascular diseases and metabolic disorders. This study examines the effects of supplementation of black pepper (Piper nigrum) which contains piperine a bioactive compound as its prominent constituent, on lipid profile parameters in NAFLD patients over 12 weeks. A randomized, double-blind, placebo-controlled trial was conducted with 170 clinically and radiologically diagnosed NAFLD patients. Participants were randomly allocated into a piperine supplementation group (n=85) and a placebo group (n=85). Lipid profile parameters, including total cholesterol, triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL), were measured at baseline and post-intervention using enzymatic colorimetric analysis. The piperine group exhibited a significant reduction in total cholesterol, triglycerides, and LDL, along with a marked increase in HDL levels, whereas the placebo group showed no significant changes. Percent Changes in Lipid Profile (Piperine Group): Total Cholesterol ↓15.13%, Triglycerides ↓44.94%, LDL ↓21.58%, HDL ↑3.51%. The findings suggest that piperine supplementation could be an effective adjunct in managing lipid profiles in NAFLD patients, potentially reducing dyslipidemia-related complications. Further studies are required to assess long-term safety and underlying mechanisms.